Fiscal and Debt Management in Andhra Pradesh (India) : An Update on the Reform Program - Swaroop, Vinaya; Dasgupta, Shatanjaya (World Bank, Washington, DC, 2013)
The main objective of this fiscal note is to assist the Government of Andhra Pradesh (GoAP) in meeting the challenges mentioned above. To this end, it provides input into the state's rolling medium-term fiscal framework exercise. The new Fiscal Responsibility and Budget Management (FRBM) act requires that the government will lay out in each financial year a medium-term fiscal policy statement (together with three-year rolling targets for key fiscal indicators) before the state legislature. In addition, this fiscal note provides the needed analytical underpinning for the Bank's ongoing development policy lending program in the state. The remainder of this note is organized as follows. The next section looks at the state's performance in improving its fiscal balance. Section three looks at the revenue performance of the state with a particular emphasis on the newly implemented Value Added Tax (VAT). The size and composition of expenditures is analyzed next (section four) with a close examination of the government's new priority expenditure on adding new irrigation schemes. Section five briefly looks at the debt and examines issues related to debt sustainability. Section six concludes.